Native renal biopsy: outcomes with a 4‐h observation period in low‐risk outpatients. Issue 1 (20th January 2022) - Trinh, Katie; Bency, Rosamma; Kairaitis, Lukas
Abstract: Current practice guidelines recommend that 'low‐risk' outpatients undergoing percutaneous native renal biopsy (PRB) are observed for 6–8 h to identify post‐biopsy complications. We performed a retrospective review of 225 PRB procedures in low‐risk outpatients who were observed for a 4‐h period to determine the safety with regard to complication rate and timing. PRB was performed using a standardised protocol and under ultrasound guidance with a 16‐ or 18‐gauge needle. Bleeding complications occurred in 7% (16/225) of patients, of which 88% (14/16) were detected within a 4‐h period. The two undetected complications presented more than 72 h after the procedure. This suggests that a 4‐h observation period may be safe and adequate in identifying the majority of patients who will experience significant complications in the first 24 h, with a potential saving of time and resources.